2015
DOI: 10.1007/s10646-015-1437-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of chlorophyll derivatives to control parasites in aquatic ecosystems

Abstract: Several research groups have studied new biopesticides which are less toxic to the environment and capable of controlling the vectors of parasitic diseases, especially in aquatic ecosystems. Pest control by photodynamic substances is an alternative to chemical or other measures, with chlorophyll and its derivatives as the most studied substances supported by their easy availability and low production costs. The impact of chlorophyll derivatives on four different species, a small crustacean (Daphnia similis), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…It is reported that chlorophyllin was able to kill four different species, a small crustacean (Daphnia similis), a unicellular alga (Euglena gracilis) and two species of fish (Astyanax bimaculatus and Cyprynus carpio) the vector of parasitic diseases. 19 Although it has been reported 19 that chlorophyllin is toxic against Astyanax bimaculatus and Cyprynus carpio, yet in our observation it is not toxic against C. fasciatus. Both extracted and pure chlorophyllin are more effective in summer than winter.…”
Section: Resultscontrasting
confidence: 56%
“…It is reported that chlorophyllin was able to kill four different species, a small crustacean (Daphnia similis), a unicellular alga (Euglena gracilis) and two species of fish (Astyanax bimaculatus and Cyprynus carpio) the vector of parasitic diseases. 19 Although it has been reported 19 that chlorophyllin is toxic against Astyanax bimaculatus and Cyprynus carpio, yet in our observation it is not toxic against C. fasciatus. Both extracted and pure chlorophyllin are more effective in summer than winter.…”
Section: Resultscontrasting
confidence: 56%
“…Chlorophylls should be incubated in dark conditions for a few hours to accumulate in the larvae and subsequent exposure to light, for example applying chlorophyll derivatives to water at night, which will be accumulated in larvae and photodynamic reaction will start with the sunrise [7]. In this sense, chlorophyllin and pheophorbide are fatal to larvae of Culex and Chaoborus [125], chlorophyllin effectively kills Aedes and Anopheles species [126] and even chlorophyll derivatives are effective against the larvae of freshwater snail [127] and certain parasites of fish [128].…”
Section: )-Metiated Pdt With Halogen Light Has Inactivated Various Smentioning
confidence: 99%
“…Photolarvicidal activity of red spectral band irradiated Pa was followed by white and sunlight irradiance. It has been advocated by various scientists that chlorophyll derivatives like chlorophyllin and pheophorbide show more photomediated control of disease caused by mosquito and insect larvae [12, 13, 16]. The EC 50 values exposed to pheophorbide for 3 h to a light intensity of 147 W/m 2 were 8.44 mg/L and 1.05 mg/L against Culex and Chaoborus mosquito larvae, respectively [11].…”
Section: Discussionmentioning
confidence: 99%